Moderate Islam in Online Speech: A Textual Studies of The Arrahim.id - Taufiqurrohman; Alindah, Lutfiyah (Proceedings of International Conference on Islamic Civilization and Humanities, 2023)
In recent years, the issue of moderate Islam has gained significant importance due to the rise of radicalism and extremism, which have disrupted social harmony in various parts of the world. As one of the major sources of religious understanding, In Indonesia, a country with a predominantly Muslim population, the dissemination of religious knowledge through Friday sermons plays a crucial role in influencing the mindset of the Muslim community. Understanding the significance of studying the textual content of Friday sermons disseminated online becomes essential for a comprehensive analysis of the phenomenon. This paper addresses the central question: “How is the concept of Moderate Islam interpreted and conveyed within the textual content of The Arrahim.id’s Friday sermons?” Utilizing Roland Barthes’ Semiotics, this study interprets both denotative and connotative texts in the sermon content displayed on the website Arrahim.id, with the object of analyzing Moderate Islam. Furthermore, the research aims to capture how these texts promote an inclusive, harmonious, and respectful understanding of Islam among Muslims and the wider community. The findings of the study indicate that the denotative meaning of tolerant Islam is based on the teachings of the Quran, Hadith, and Islamic attitudes. On the other hand, the connotative meaning within the sermon texts portrays the image of Islam as Rahmatan lil’alamin representing Moderate Islam. This meaning is then elaborated through moderate attitudes and practices. However, moderate Islam views personal purity and social engagement as interconnected elements in expressing faith. By prioritizing love and compassion for others, believers embody the true essence of Islamic teachings and contribute to the betterment of society.